The Influence of Spada Learning Management System (LMS) on Algorithm Learning and Programming of First Grade Students at Universitas Pendidikan Indonesia - Husaeni, Dwi Novia Al; Hadianto, Daris (Universitas Pendidikan Indonesia (UPI), 2022)
This study discusses the effect of using a Learning Management System (LMS) on learning Algorithms and Programming. This study aims to determine the effectiveness of the LMS Spada in the Algorithm and Programming learning process, to determine the positive and negative impacts of using LMS, and to find out how to improve the learning process to make it more effective. The method in this study is a survey method with 32 participants. The data was obtained from distributing questionnaires through WhatsApps social media. The results of this study, it is known that LMS is very effective in learning Algorithms and Programming. Then in this study it was also stated that the use of LMS in the learning process had a positive impact and a negative impact. In addition to knowing the effectiveness, positive and negative impacts, in this study we can find ways to improve the learning process to be more effective, including: Continue to practice and read, be brave, take advantage of existing learning media, complete facilities and infrastructure and others.